2003
DOI: 10.1007/s00535-003-1180-1
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of fulminant hepatitis B in immunocompromised hemodialysis patients

Abstract: This outbreak of fulminant hepatitis B suggests that HD patients can foster highly virulent HBV strains (possibly owing to their compromised immune responses), which may place others at risk of severe, life-threatening acute liver damage and at increased risk of mortality if chronic carriers of HCV should be infected. We aimed to clarify the pathogenesis of an outbreak of fulminant hepatitis B in hemodialysis (HD) patients whose compromised cell-mediated immunity in turn contributed to chronic hepatitis B viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…In addition, numerous in vivo and in vitro experiments have shown that the impaired response to the HBV vaccine in uremic individuals has been related to additional factors: a lower activation of T-lymphocytes (naïve CD4) to helper cells by overproduction of TNF-α, re- According to our systematic review, reinforced schedules of the HB vaccine enhance the response rate in uraemic patients. This phenomenon is particularly clear 6 Hepat Mon. 2017; 17 (7):e44179.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, numerous in vivo and in vitro experiments have shown that the impaired response to the HBV vaccine in uremic individuals has been related to additional factors: a lower activation of T-lymphocytes (naïve CD4) to helper cells by overproduction of TNF-α, re- According to our systematic review, reinforced schedules of the HB vaccine enhance the response rate in uraemic patients. This phenomenon is particularly clear 6 Hepat Mon. 2017; 17 (7):e44179.…”
Section: Discussionmentioning
confidence: 98%
“…On the contrary, prevalence and incidence rates of HBV remain high within dialysis facilities of the developing world (5). In addition, outbreaks of the HBV infection among patients undergoing long-term hemodialysis continue to be reported in industrialized countries (6). To prevent transmission of HBV in haemodialysis units, numerous measures have been performed including the screening of blood for the hepatitis B surface antigen (HBsAg), the decline in the number of blood transfusions, and the implementation of universal and specific measures within dialysis rooms, as recommended by the centers for disease control and prevention (CDC, Atlanta, Georgia, USA) (7).…”
Section: Contextmentioning
confidence: 99%
“…Up to 60% of infected patients on haemodialysis are not able to clear the virus and therefore become chronic HBV carriers [92]. Moreover, even though patients are vaccinated and appropriate measures to prevent transmission of the virus have been put in place, HBV outbreaks in dialysis centres still occur [93,94].…”
Section: Hbvmentioning
confidence: 99%
“…Up to 60% of infected patients on haemodialysis are not able to clear the virus and therefore become chronic HBV carriers [92]. Moreover, even though patients are vaccinated and appropriate measures to prevent transmission of the virus have been put in place, HBV outbreaks in dialysis centres still occur [93,94].In the normal healthy population, long-term protection relies on immune memory in humans reaching anti-HBs concentrations ≥10 mIU/mL post vaccination.For immunocompromised individuals, protection against HBV infection relies more on circulating antibodies [95]. Studies in haemodialysis patients showed that many patients with anti-HBs levels between 10 and 100 mIU/mL did not retain protective antibody level of ≥10 mIU/mL one year post vaccination.…”
mentioning
confidence: 99%
“…The implementation of routine screening of blood derived products, and infection control practices including universal precautions, separate rooms and separate machines for HBsAg positive patients have sharply reduced the incidence of HBV infection in dialysis units [2,3], even if outbreaks continue to occur in chronic haemodialysis centers [4,5]. In addition, HBV vaccination has been recommended for all sero-negative dialysis members and staff members since the early 1980s [2,3].…”
Section: Introductionmentioning
confidence: 99%